Technology as a Catalyst for Improving Soldier Professionalism in Modern Warfare - Iwan Permana, Setyo Widagdo, M. Nuh, M. Kholid Mawardi (South Eastern European Journal of Public Health, 2025)
This qualitative research explores the role of technology in enhancing soldier professionalism. Utilizing expert interviews, document analysis, and observations, the study applies the qualitative data analysis framework developed by Miles and Huberman. The findings indicate that advancements in combat technology significantly impact the education, training, and assignment of soldiers within military organizations. Despite challenges such as infrastructure limitations and training deficiencies, the potential to leverage technology for improving soldier professionalism is substantial. Therefore, military organizations must adopt appropriate strategies to adapt to these changes and maintain operational effectiveness. Key factors in enhancing performance and professionalism in the modern era include flexibility, collaboration, and innovation. This study underscores the necessity for military institutions to embrace technological advancements not only as a means of improving traditional skills but also as a critical component in preparing soldiers for the complexities of contemporary warfare. By fostering an environment that encourages continuous learning and adaptation to new technologies, military organizations can ensure their personnel are proficient in utilizing cutting-edge tools and systems in the field.